Keselarasan Rencana Strategis Sekolah Dengan Rencana Pelaksanaan Pembelajaran (RPP) PAI di SMK Ma’arif 4 Kebumen - Hindun Farkhah; Siti Sofiatun; Ummi Khairun Nisa; M. Faiz Fatikhun Ni’am; Syarif Hidayat; Agus Salim Chamidi; Umi Arifah; Siti Fatimah (IAINU Kebumen, 2026)
This study aims to analyze the planning of the Field Work Practice (PKL) program at SMK Ma’arif 4 Kebumen, which is systematically designed to enhance students’ competencies and work ethics. This research employed a qualitative descriptive approach with data collected through interviews, observations, and documentation involving the school principal, supervising teachers, PKL students, and industry partners. The results revealed that the PKL program planning at SMK Ma’arif 4 Kebumen was carried out through several structured stages: pre-placement briefing, student placement in industries, implementation of a batch system, selection criteria for internship locations, supervision and evaluation, and final reporting. The batch system proved effective in ensuring equitable placement and maintaining supervision quality, while cooperation with industries through Memorandums of Understanding (MoU) strengthened program relevance and sustainability. Supervision was conducted collaboratively between teachers and industry supervisors, emphasizing students’ discipline, work ethics, and responsibility. The PKL program not only focused on technical skills but also integrated Islamic character development aligned with the school’s vision, “Firm in Faith, Excellent in Achievement, and Noble in Character.” Therefore, the PKL program at SMK Ma’arif 4 Kebumen serves as an integrative model combining vocational education and Islamic values to prepare professional, independent, and morally upright graduates. Keywords: PKL Planning, Vocational Education, Industry Collaboration, Islamic Character